Perancangan sistem informasi persediaan bahan baku berbasis website pada PT. Multi Mortar - Saryani, Saryani; Junior, Fabio; Petriyansyah, Septa (JOURNAL INFORMATION TECHNOLOGY ENGINEERING AND SCIENCE, 2022)
In the context of modern business, information technology is the main key to operational success. This research highlights the important role of computerized systems in raw material inventory management at PT. Multi Mortar. Even though the stock card system is used, the manual data processing process using Microsoft Excel is often inefficient and less accurate. Lack of optimal inventory data can hinder management decision making. This study proposes designing a website-based raw material inventory system using Unified Modeling Language (UML) to fix this problem. Qualitative methods, including observational analysis, interviews, and literature studies, were used to design a system that facilitates data input and produces efficient reports. The hope is that the implementation of this new website-based system will help PT. Multi Mortar increases its operational effectiveness and enables management to make better decisions based on accurate and timely information. Thus, this research shows the importance of the integration of advanced information technology in improving business efficiency and overcoming challenges in inventory management. Keywords: Inventory, efficient, UML, Website